Analysis of Physical Resistance of Apple Tomatoes After Exposed to A Magnetic Field Extremely Low Frequency (ELF) Intensity 600 ÂµT and 1000 ÂµT - Sudarti Sudarti; Siti Umayatul Khoiroh Nur; Elok Permatasari; Nila Mutia Dewi; Sherly Nur Laili (Jurnal Penelitian Pendidikan IPA, 2022)
Apple tomatoes with the scientific name Lycopersicum Pyriporme can last 7 days at room temperature and 14 days if stored in the refrigerator. The purpose of this study was to examine the effect of the ELF magnetic field intensity 600 uT and 1000 uT for 30, 60 and 90 minutes on the degree of acidity (pH), density (Ï) and physical quality of apple tomatoes. The research design used was RAL (completely randomized design). Data collection on the pH variable begins with crushing the tomatoes and then measuring the pH value of each fruit using a digital pH meter. The density variable was obtained by weighing the mass of each fruit and dipping the fruit in 150 ml of distilled water as the initial volume, then the difference between the final volume and the initial volume was obtained to obtain the final density of each fruit using the density equation. Physical condition variables can be obtained by counting the number of good fruits and recording each measurement. Observations were made for 20 days with data collection on the 0, 4th, 8th, 16th, and 20th days. The results showed that there were differences in the value of pH, density and physical quality of tomatoes between the control group and the experimental group. Exposure to the ELF magnetic field can affect the activity and reproduction of pathogenic microorganisms in apple tomatoes so as to maintain the pH value, density and physical quality of apple tomatoes.